Lipid degradation and photosynthetic traits after prolonged darkness in four Antarctic benthic diatoms, including the newly described species Planothidium wetzelii sp. nov. - Juchem, Desirée P.; Schimani, Katherina; Holzinger, Andreas; Permann, Charlotte; Abarca, Nélida; Skibbe, Oliver; Zimmermann, Jonas; Graeve, Martin; Karsten, Ulf (Frontiers in Microbiology, 2023)
In polar regions, the microphytobenthos has important ecological functions in shallow water habitats such as on top of coastal sediments. This community is dominated by benthic diatoms, which contribute a major part of the primary production and biogeochemical cycling, and at the same time forms an important component of polar food webs. Polar diatoms are able to cope with marked seasonally changing light conditions and prolonged periods of darkness during the polar night in Antarctica. However, the underlying mechanisms are poorly understood. In this study, five strains of Antarctic benthic diatoms were isolated in the field, the resulting unialgal cultures identified as four distinct species of which one is described as a new species, Planothidium wetzelii sp. nov. All four species were thoroughly examined using physiological, cell biological and biochemical methods over a fully controlled dark period of three months. The results showed that the utilization of storage lipids is one of the key mechanisms in Antarctic benthic diatoms to survive the polar night, although different fatty acids were involved in the investigated taxa. In all tested species, the storage lipid content declined significantly, along with an ultrastructural observable degradation of the chloroplasts. Surprisingly, photosynthetic performance did not change significantly despite the chloroplasts decreasing in thylakoid membranes and an increased number of plastoglobules. Thus, a combination of biochemical and cell biological mechanisms allows Antarctic benthic diatoms to survive the polar night.